2019
DOI: 10.1002/nme.6165
|View full text |Cite
|
Sign up to set email alerts
|

An energy‐stable mixed formulation for isogeometric analysis of incompressible hyperelastodynamics

Abstract: Summary We develop a mixed formulation for incompressible hyperelastodynamics based on a continuum modeling framework recently developed in the work of Liu and Marsden and smooth generalizations of the Taylor‐Hood element based on nonuniform rational B‐splines (NURBSs). This continuum formulation draws a link between computational fluid dynamics and computational solid dynamics. This link inspires an energy stability estimate for the spatial discretization, which favorably distinguishes the formulation from th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 59 publications
(178 reference statements)
0
14
0
Order By: Relevance
“…Under the above assumption, we do not distinguish between the reference and current frames, allowing the total and partial time derivatives in (2.1)-(2.3) to be used interchangeably. Furthermore, β θ (p s ) = 1/κ s , where κ s is the solid bulk modulus, and (2.2) can be integrated to yield p s = −κ s ∇ • u s [19].…”
Section: Strong-form Fsi Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the above assumption, we do not distinguish between the reference and current frames, allowing the total and partial time derivatives in (2.1)-(2.3) to be used interchangeably. Furthermore, β θ (p s ) = 1/κ s , where κ s is the solid bulk modulus, and (2.2) can be integrated to yield p s = −κ s ∇ • u s [19].…”
Section: Strong-form Fsi Problemmentioning
confidence: 99%
“…For improved representation of the Schur complement, we apply the nested block preconditioner [25] that algorithmically defines the action of the Schur complement on a vector in a matrix-free fashion. We have demonstrated enhanced robustness and scalability of our block preconditioner as compared to alternative preconditioners in applications spanning hyperelasticity, viscous fluids, and FSI [19].…”
Section: Solution Strategymentioning
confidence: 99%
“…For fully incompressible materials, it can be shown that the volumetric part of the free energy adopts the form G ∞ vol = P/ρ 0 [55], which leads to ρ = ρ 0 . In the formulation, we adopt a modified constitutive relation for the density, that is ρ(J) = ρ 0 /J [60]. Apparently, at the continuum level, this relation is equivalent to ρ(J) = ρ 0 , as the divergence-free condition for the velocity guarantees J = 1.…”
Section: Strong-form Problemmentioning
confidence: 99%
“…The aforementioned Gibbs free energy can be viewed as the thermodynamic explanation of the effectiveness of the pressure primitive variables. A theory for finite elasticity based on the Gibbs free energy has been established [55]; the saddle-point nature has been exploited to design preconditioners [58,59]; it can also be shown to enjoy a provably nonlinearly stable semi-discrete formulation using inf-sup stable elements [60]; it can be conveniently utilized to construct a strongly-coupled fluid-structure interaction formulation [55,61]. In this work, we follow our prior approach and use the Gibbs free energy to construct a mixed formulation for viscoelastodynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation